V2O5 nanobelt arrays with controllable morphologies for enhanced performance supercapacitors. Issue 43 (11th October 2017) - Xu, Jiahe; Zheng, Feng; Gong, Hanqin; Chen, Lai; Xie, Jiaheng; Hu, Pengfei; Li, Yang; Gong, Yu; Zhen, Qiang
Abstract : Controllable preparation of V2 O5 nanobelt arrays as binder-free supercapacitive electrode materials and their charge–discharge mechanism. Abstract : Ordered V2 O5 nanobelt arrays (VNBs) vertically grown on Ni foam have been realized by one-step hydrothermal method without any additives. The obtained VNBs are a single crystal with a two-dimensional (2D) layered structure. The morphology evolution and growth mechanism of VNBs are discussed at different hydrothermal times. The morphologies, length–width ratios and sizes of materials can be controlled by simply adjusting vanadium source concentrations, pH values and hydrothermal temperatures. Moreover, these morphology parameters can significantly affect specific capacitance, cycle stability and charge transfer resistance. Due to the ordered arrangement, single-crystal, top–down and layered structure, VNBs have a relatively high ion storage capacity, specific capacitance (498 F g −1 ), cycling stability (88.8%) after 5000 cycles and low charge transfer resistance (14.2 Ω) as binder-free electrode materials, which reveals a great potential for practical application in energy storage devices.